Мікропорова структура моркви - Вербицький, Борис Ілліч; Луцик, Юрій Павлович; Левківська (Музика), Тетяна Миколаївна (My University, 2013)
В статті наведені визначені для моркви об’єм мікропор, інтегральні та диференціальні криві розподілу мікропор за радіусами, ефективний радіус пор, питома поверхня. Показано їх вплив на процес сушіння. It is stated, that the volume of micropores increases from the minimal radius by the parabolic low up to value ≈ 120∙10-10 m, and then the dependence has linear form. It is shown, the micropores with smallest radius 10∙10-10 m are predominated in the fresh carrot, the value of effective radius is ≈ 50∙10-10 m, the value of specific surface - – 156 m2/g. It is stated, that all capillary moisture and partially moisture of polymolecular adsorption has been took away during the process of drying to standard moisture content.
Keywords: питома поверхня; сушіння; морква; розподіл мікропор; specific surface; drying; carrot; micropores; pores distribution; кафедра фізики та професійної безпеки; кафедра технології консервування